Lessons at the school by the sea - Colgan, Jenny (Colgan, Jenny. School by the sea, 2023)
"School is out, following a bit of saucy scandal at Downey House ... Beloved high school teacher Maggie Adair had been comfortably, if somewhat ambivalently, engaged to her dependable long-distance boyfriend Stan. But in the heat of summer, Maggie's attraction to her colleague David McDonald has caught fire. Now both are facing an uncertain future as they try to figure out how to stay committed to their careers--and each other. Meanwhile, the girls of Downey House--mercurial Fliss, glamorous Alice, and shy, hard-working Simone--have had long summers at home, which weren't quite the respite they had been hoping for. But the new school year is thankfully here, and it will bring new pupils and lots of fresh challenges for students and teachers alike at the school by the sea."--